Scaffolding spatial problem solving in science: Guidelines derived from theory and research - Christos-Vonapartis KOSMIDIS; Nikos LAMBRINOS (European Journal of Geography)
Spatial skills have been recognized as a predictor of achievement and performance in Science disciplines. These skills are expressed through different problem-solving strategies, depending on content, students’ characteristics and provided representations. The purpose of this article is to identify critical issues in scaffolding students’ spatial problem solving in science, based on the development of alternative strategies through the interaction with multiple representations. Perceiving representations as tools, their beneficial effect on problem-solving is interpreted through the mediated action theory. Taking into account cognitive and developmental theories and research findings, a framework that includes critical dimensions, like representations’ characteristics and students’ age, is proposed. Finally, we consider the possible potential of geospatial representations for introducing students in science problem-solving and conclude by examining implications for research.